2019
DOI: 10.1007/s00455-019-10066-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Lingual Resistance Training Interventions on Adult Swallow Function: A Systematic Review

Abstract: Lingual resistance training has been proposed as an intervention to improve decreased tongue pressure strength and endurance in patients with dysphagia. However, little is known about the impact of lingual resistance training on swallow physiology. This systematic review scrutinizes the available evidence regarding the effects of lingual resistance training on swallowing function in studies using Videofluoroscopic Swallowing Studies (VFSS) with adults. Seven articles met the inclusion criteria and underwent de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 46 publications
1
30
0
Order By: Relevance
“…The pre-and post-training comparisons of the exercise group showed a significant improvement of 4.1 kPa in MTP (an 11.53% increase) and 4.53 s in ETP (a 99.86% increase). Previous studies have already shown that TSE with this device increases MTP [7,8]. Previous studies in healthy older adults using a tongue strength training device have shown improvements in MTP from 18 to 72% [11-13, 25, 30].…”
Section: %-85% N=3mentioning
confidence: 83%
See 2 more Smart Citations
“…The pre-and post-training comparisons of the exercise group showed a significant improvement of 4.1 kPa in MTP (an 11.53% increase) and 4.53 s in ETP (a 99.86% increase). Previous studies have already shown that TSE with this device increases MTP [7,8]. Previous studies in healthy older adults using a tongue strength training device have shown improvements in MTP from 18 to 72% [11-13, 25, 30].…”
Section: %-85% N=3mentioning
confidence: 83%
“…This study showed that MTP and ETP significantly increased in healthy older adults after the 8 weeks of TSsE using the tongue-strengthening self-exercise tool at home. Previous studies have shown that TSE increased the MTP in stroke patients, patients with acquired brain injury, and healthy participants [7,8]. In particular, many studies have examined TSE using devices and substantial evidence of its efficacy has been accumulated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A preliminary study on the efficacy of lingual resistance training in two patients with ALS showed no improvement in swallowing safety and patient‐reported outcome, but swallowing efficacy was not included in the outcomes of the study 43 . A recent systematic review on different populations highlighted that the effects of lingual resistance training on both swallowing safety and swallowing efficacy are still controversial 44 . Thus, the feasibility and efficacy of lingual resistance training in ALS need to be further tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Our results revealed that there was no signi cant difference between the sarcopenia group and their healthy counterparts regarding tongue pressure. Studies have reported that tongue strengthening could enhance the maximum peak lingual pressures in both healthy adults and dysphagic patients; however, whether the gain in lingual pressures generalizes to the functional improvement in swallowing is still undetermined (36,37). A previous study done in Japan demonstrated that reduced tongue pressure is correlated with older individuals with sarcopenia (9); however, 42.3% of their subjects suffered from dysphagia, and all their subjects were hospitalized at the time of enrollment.…”
Section: Discussionmentioning
confidence: 99%